Digital Transformation Dynamics: A Comprehensive Analysis of Financial Climate Risk and Leverage on Digital Asset Performance in the Fintech Ecosystem - Ajmilia, Qori Fadla; Gea, Edi Zaman Berkat; Sadalia, Isfenti (Jurnal Bisnis dan Manajemen West Science, 2025)
This study investigates the impact of financial climate risk and financial leverage on digital asset performance within the Indonesian fintech ecosystem. Employing an explanatory quantitative approach with a cross-sectional design, the research analyzed 18 digital financial institutions, including digital banks, fintech platforms, cryptocurrency platforms, digital startups, and digitally transforming conventional banks. Data was collected from secondary sources covering the period 2021-2024, utilizing the Climate Vulnerability Index (CVI), Debt to Equity Ratio (DER), and Digital Asset Performance Index (DAPI). Multiple linear regression analysis was conducted using SPSS to examine the relationships between variables. The findings reveal significant correlations between financial climate risk, financial leverage, and digital asset performance. Climate Vulnerability Index demonstrated a negative relationship, while Debt to Equity Ratio showed a positive relationship with digital asset performance. The research contributes to understanding the complex dynamics of digital financial ecosystems, offering insights for strategic investment and risk management in the evolving digital financial landscape.